Fe3O4@Ag core-shell composite nanoparticle with tunable optical property - Thananchai Dasri; Artit Chingsungnoen (Research & Knowledge, 2018)
In this work, plasmonic behaviors exhibited by nanoparticles (NP) composed of magnetite (Fe3O4 ) cores with silver (Ag) shells were investigated by discrete dipole approximation (DDA). First, the Fe3O4 core size was ixed at 32 nm and the Ag shell thickness was varied from 8 nm to 15 nm. Second, the Ag shell thickness was ixed at 16 nm and the Fe3O4 core diameters were between 5 and 20 nm. The calculated absorption peaks showed two peaks positioned to the left and right of 382 nm, which is the peak position of pure Ag. The results revealed that by varying either the Fe3O4 core size or the Ag shell thickness compared with pure Fe3O4 and Ag NP, light absorption enhancement and tunable aspects are successfully achieved. This nanomaterial is expected to be applicable in biomedicine, nanocatalysis, optic devices, and new functional devices in the future.